Mcuabsensi Pemanfaatan Hostpot Nodemcu, Aplikasi Android, Dan Raspberry Untuk Pengambilan Absensi Online - Afdal; Rika Idmayanti; Cipto Prabowo (SOTVI - Society of Visual Informatics, 2020)
Online attendance system with the use of raspberries as a local server to synchronize system data on the server and attendance data processing, nodemcu as a tool that can transmit hostpot signals for attendance and android connected to the nodemcu hostpot with the android application for each event attendance in taking attendance . In this system Attendance can be taken at a distance of less than 30 meters by utilizing the nodemcu hostpot signal, an attendance device with additional battery power in anticipation of a main power outage, a local Raspberry pi server that is always synchronized with a public server so that when the internet network dies requesting attendance can still be processed and stored, the application that stores the mac address of the event participants so that there is only one warak on one user to minimize attendance cheating fraud, attendance taking and event permits can be done on the android application, taking attendance allows can be taken together to overcome attendance taking . This attendance system utilizes Restfult API technology with JavaScript Express programming framework, microcontroller with Arduino IDE C programming, websites with React.js JavaScript programming framework, and android applications with React Native JavaScript programming. In the design of this attendance system has several methods, namely problem identification, literature study, consultation, system analysis, system design, and implementation. The result of this system is a system that can streamline the taking and minimize attendance fraud